triclino Posted May 26, 2010 Posted May 26, 2010 Prove using contradiction the following: [p<=>(q <=>r)] =>[(p<=>q)=> r]
shyvera Posted May 26, 2010 Posted May 26, 2010 Use the following rules: [math]a\Leftrightarrow b\ \equiv\ (a\wedge b)\vee(\neg a\wedge \neg b)[/math] [math]\neg(a\Leftrightarrow b)\ \equiv\ (a\wedge \neg b)\vee(\neg a\wedge b)[/math] Thus: [math]\neg[(p\Leftrightarrow q)\Rightarrow r][/math] [math]\implies\ (p\Leftrightarrow q)\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\vee(\neg p\wedge\neg q)]\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\wedge\neg r]\vee[(\neg p\wedge\neg q)\wedge\neg r][/math] [math]\implies\ [p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)][/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}\vee\{[p\wedge(\neg q\wedge r)]\vee[\neg p\wedge(q\wedge r)]\}[/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[p\wedge(\neg q\wedge r)]\}\vee\{[\neg p\wedge(q\wedge r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}[/math] [math]\implies\ \{p\wedge[(q\wedge\neg r)\vee(\neg q\wedge r)]\}\wedge\{\neg p\wedge[(q\wedge r)\vee(\neg q\wedge\neg r)]\}[/math] [math]\implies\ [p\wedge\neg(q\Leftrightarrow r)]\wedge[\neg p\wedge(q\Leftrightarrow r)][/math] [math]\implies\ \neg[p\Leftrightarrow(q\Leftrightarrow r)][/math]
triclino Posted May 26, 2010 Author Posted May 26, 2010 Use the following rules: [math]a\Leftrightarrow b\ \equiv\ (a\wedge b)\vee(\neg a\wedge \neg b)[/math] [math]\neg(a\Leftrightarrow b)\ \equiv\ (a\wedge \neg b)\vee(\neg a\wedge b)[/math] Thus: [math]\neg[(p\Leftrightarrow q)\Rightarrow r][/math] [math]\implies\ (p\Leftrightarrow q)\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\vee(\neg p\wedge\neg q)]\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\wedge\neg r]\vee[(\neg p\wedge\neg q)\wedge\neg r][/math] [math]\implies\ [p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)][/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}\vee\{[p\wedge(\neg q\wedge r)]\vee[\neg p\wedge(q\wedge r)]\}[/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[p\wedge(\neg q\wedge r)]\}\vee\{[\neg p\wedge(q\wedge r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}[/math] [math]\implies\ \{p\wedge[(q\wedge\neg r)\vee(\neg q\wedge r)]\}\wedge\{\neg p\wedge[(q\wedge r)\vee(\neg q\wedge\neg r)]\}[/math] [math]\implies\ [p\wedge\neg(q\Leftrightarrow r)]\wedge[\neg p\wedge(q\Leftrightarrow r)][/math] [math]\implies\ \neg[p\Leftrightarrow(q\Leftrightarrow r)][/math] Where is the contradiction
shyvera Posted May 27, 2010 Posted May 27, 2010 You are assuming [math][p\Leftrightarrow(q\Leftrightarrow r)]\Rightarrow[(p\Leftrightarrow q)\Rightarrow r][/math] to be false. This is equivalent to [math][p\Leftrightarrow(q\Leftrightarrow r)]\wedge\neg[(p\Leftrightarrow q)\Rightarrow r].[/math] What I did was to show that [math]\neg[(p\Leftrightarrow q)\Rightarrow r][/math] would lead to [math]\neg[p\Leftrightarrow(q\Leftrightarrow r)][/math] which would make a contradiction with [math]p\Leftrightarrow(q\Leftrightarrow r).[/math]
triclino Posted May 27, 2010 Author Posted May 27, 2010 Use the following rules: [math]a\Leftrightarrow b\ \equiv\ (a\wedge b)\vee(\neg a\wedge \neg b)[/math] [math]\neg(a\Leftrightarrow b)\ \equiv\ (a\wedge \neg b)\vee(\neg a\wedge b)[/math] Thus: [math]\neg[(p\Leftrightarrow q)\Rightarrow r][/math] [math]\implies\ (p\Leftrightarrow q)\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\vee(\neg p\wedge\neg q)]\wedge\neg r[/math] [math]\implies\ [(p\wedge q)\wedge\neg r]\vee[(\neg p\wedge\neg q)\wedge\neg r][/math] [math]\implies\ [p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)][/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}\vee\{[p\wedge(\neg q\wedge r)]\vee[\neg p\wedge(q\wedge r)]\}[/math] [math]\implies\ \{[p\wedge(q\wedge\neg r)]\vee[p\wedge(\neg q\wedge r)]\}\vee\{[\neg p\wedge(q\wedge r)]\vee[\neg p\wedge(\neg q\wedge\neg r)]\}[/math] [math]\implies\ \{p\wedge[(q\wedge\neg r)\vee(\neg q\wedge r)]\}\wedge\{\neg p\wedge[(q\wedge r)\vee(\neg q\wedge\neg r)]\}[/math] [math]\implies\ [p\wedge\neg(q\Leftrightarrow r)]\wedge[\neg p\wedge(q\Leftrightarrow r)][/math] [math]\implies\ \neg[p\Leftrightarrow(q\Leftrightarrow r)][/math] So now let us examine your proof: According to your rule (which you must show how you get): [math]\neg(a\Leftrightarrow b)\ \equiv\ (a\wedge \neg b)\vee(\neg a\wedge b)[/math] To get :[math] \neg[p\Leftrightarrow(q\Leftrightarrow r)][/math] You must have :[math] [p\wedge\neg(q\Leftrightarrow r)]\vee[\neg p\wedge(q\Leftrightarrow r)][/math] Instead of [math] [p\wedge\neg(q\Leftrightarrow r)]\wedge[\neg p\wedge(q\Leftrightarrow r)][/math] That you have in your proof
Recommended Posts
Create an account or sign in to comment
You need to be a member in order to leave a comment
Create an account
Sign up for a new account in our community. It's easy!
Register a new accountSign in
Already have an account? Sign in here.
Sign In Now